1995
DOI: 10.1029/95jc02554
|View full text |Cite
|
Sign up to set email alerts
|

Solar heating of the Arctic mixed layer

Abstract: Data from the 1975 Arctic Ice Dynamics Joint Experiment (AIDJEX) are used to examine energy exchange between the Arctic mixed layer and the ice pack. Conductivity‐temperature‐depth profiles from four drifting stations reveal significant heat storage in the upper 50 m of the water column during summer, with mixed layer temperature elevation above freezing δT reaching as high as 0.4°C. Combining δT with turbulent friction velocity obtained from local ice motion provides an estimate of heat flux from the ocean to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
203
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(228 citation statements)
references
References 27 publications
12
203
3
Order By: Relevance
“…Surface ablation in ponded ice was notably greater, totaling 85 cm. During AIDJEX the average ablation for unponded ice was 26 cm on the surface and 34 cm on the bottom (Maykut and McPhee, 1995). Total ablation during SIMI was 50% greater than observed during AIDJEX and nearly double that observed during Alpha II on unponded ice.…”
Section: Temperaturementioning
confidence: 83%
See 1 more Smart Citation
“…Surface ablation in ponded ice was notably greater, totaling 85 cm. During AIDJEX the average ablation for unponded ice was 26 cm on the surface and 34 cm on the bottom (Maykut and McPhee, 1995). Total ablation during SIMI was 50% greater than observed during AIDJEX and nearly double that observed during Alpha II on unponded ice.…”
Section: Temperaturementioning
confidence: 83%
“…This is due, in large part, to the expense involved in operating a long-term field camp, which typically serves as the base for these studies. The combined results of four sea ice mass balance studies (Untersteiner, 1961;Hanson, 1965; Koerner, 1973;Maykut and McPhee, 1995) suggest that there is significant interannual variability in the ablation/accretion rate This paper is not subject to U.S. copyright. Published in !997 by the American Geophysical Union.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of the NSTM during AIDJEX (Maykut and McPhee, 1995) and SHEBA (McPhee et al, 1998) found that the layer was present directly below the summer surface mixed layer, at depths between 25 and 35 m. However, the Canada Basin upper ocean is freshening (McPhee et al, 2009) Summer sea ice extent in the Western Arctic has decreased significantly in recent years resulting in increased solar input into the upper ocean. Here, a comprehensive set of in situ shipboard, on-ice, and autonomous ice-ocean measurements were made of the early stages of formation of the near-surface temperature maximum (NSTM) in the Canada Basin.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of the NSTM during AIDJEX (Maykut and McPhee, 1995) and SHEBA (McPhee et al, 1998) found that the layer was present directly below the summer surface mixed layer, at depths between 25 and 35 m. However, the Canada Basin upper ocean is freshening (McPhee et al, 2009) through a combination of sea ice melt, river runoff, and convergence of Ekman boundary layer transports under the Beaufort Gyre (MacDonald et al, 1999;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation